(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article explores substantivization, the linguistic process through which adjectives take on the function of nouns. This phenomenon allows adjectives to act independently as nouns, representing broad categories of people, abstract concepts, or collective ideas. For instance, adjectives like “rich” and “poor” in English can stand alone as nouns to signify groups of people with those traits. The article explains the mechanics of substantivization, highlighting how adjectives can be pluralized, used with articles, or abstracted to refer to collective qualities. The discussion includes examples from other languages, like French and German, illustrating how this process varies across linguistic contexts and sometimes involves gender changes in languages with grammatical gender, such as Spanish. Substantivization provides efficiency and clarity in communication by enabling speakers to convey complex ideas and social identities in a streamlined form. This process also reflects cultural perspectives, allowing languages to categorize and discuss groups with shared characteristics. The article concludes by emphasizing the versatility and adaptability of substantivization as a linguistic tool that enhances expression and meets evolving communicative needs.